Analisis Pembangunan Berbasis Masyarakat- Studi Kasus CAP (Community Action Plan) di Kelurahan Kramat - Fitrinitia, Irene Sondang, Ph.D (Cities and Urban Development Journal, 2025)
Background: The Community Action Plan (CAP) has been implemented as a participatory approach to improving settlement quality through collaboration between the community and the government. Aims: This study aims to explore the CAP process in community-based development planning in Kramat Ward and to understand the role of citizen participation and synergy with government policies in enhancing settlement quality Methods: A descriptive qualitative approach with a case study method was used to analyze the process of community-based development planning. Results: The findings indicate that the Community Action Plan (CAP) enables residents to identify and propose solutions to settlement-related issues. Community-driven actions included participatory mapping, community meetings (rembug warga) to identify socio-economic and infrastructure issues, and the joint formulation of solutions. These actions resulted in program plans supported by local administrative units and neighborhood-level authorities. The integration of actors within the community and the implementation of activities required synchronization between both parties. However, challenges in program sustainability and inter-stakeholder coordination remain major obstacles to effective implementation. Conclusion: The importance of community-based development in improving the quality of settlements sustainability such as CAP program. Synergy between the community, government, and other stakeholders is essential for successful development implementation, despite ongoing challenges in program sustainability and stakeholder coordination